2021
DOI: 10.1021/acsnano.0c10185
|View full text |Cite
|
Sign up to set email alerts
|

Affinity Capture of p97 with Small-Molecule Ligand Bait Reveals a 3.6 Å Double-Hexamer Cryoelectron Microscopy Structure

Abstract: Recent progress in the development of affinity grids for cryoelectron microscopy (cryo-EM) typically employs genetic engineering of the protein sample such as histidine or Spy tagging, immobilized antibody capture, or nonselective immobilization via electrostatic interactions or Schiff base formation. We report a powerful and flexible method for the affinity capture of target proteins for cryo-EM analysis that utilizes small-molecule ligands as bait for concentrating human target proteins directly onto the gri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
13
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 51 publications
(107 reference statements)
2
13
1
Order By: Relevance
“…Thus, the p97 R155H mutant is found in additional forms, forming complexes beyond the hexameric arrangement of the wild-type protein. Although the higher-order form has been reported for the wild type [ 19 ], inhibitor-bound [ 54 , 55 ], or engineered p97 [ 56 ], we did not find the same pattern in the SEC of the wild type, possibly because the high-order complex was in a less proportion in the wild type that could not be detected. In the SDS-PAGE analysis, these higher-order complexes do not associate with p47, even in the presence of excess p47 ( Figure 1 B).…”
Section: Resultscontrasting
confidence: 84%
“…Thus, the p97 R155H mutant is found in additional forms, forming complexes beyond the hexameric arrangement of the wild-type protein. Although the higher-order form has been reported for the wild type [ 19 ], inhibitor-bound [ 54 , 55 ], or engineered p97 [ 56 ], we did not find the same pattern in the SEC of the wild type, possibly because the high-order complex was in a less proportion in the wild type that could not be detected. In the SDS-PAGE analysis, these higher-order complexes do not associate with p47, even in the presence of excess p47 ( Figure 1 B).…”
Section: Resultscontrasting
confidence: 84%
“…While the major pool of human p97 forms a hexamer, a minor population of p97 is known to exist as a double hexamer (DH), which is thought to be catalytically inactive 27 , 31 36 . Here, we show that both human p97 and yeast Cdc48 can form DHs in vitro, which are functional ATPases.…”
Section: Introductionmentioning
confidence: 99%
“…In further support of the important role of apo D2 in triggering VCP dodecamerization, we showed that a recently reported A530T mutant with markedly reduced nucleotide binding in D2 ( Her et al., 2016 ) also exhibited an increased propensity of dodecamer formation in comparison with the wild-type VCP ( Figures 4 E and 4F), which could be further enhanced by ADP depletion with apyrase. In addition, during the preparation of this article, a dodecamer structure was reported for VCP immobilized with an inhibitor-decorated cryo-EM support ( Hoq et al., 2021 ), which as revealed by the comparison in Figure S8 also contains apo D2. This again validates our conclusion.…”
Section: Resultsmentioning
confidence: 89%
“…Although the cellular regulatory mechanism(s) of VCP oligomerization remain to be fully established, we speculate that unknown factors such as post-translational modifications or ligands that can reduce or inhibit VCP nucleotide binding may stabilize the dodecamer state of VCP. A recent study reported a similar dodecamer structure of VCP determined using an inhibitor ligand-decorated affinity gird technique of cryo-EM ( Hoq et al., 2021 ). In agreement with our conclusion that apo D2 induces VCP dodecamerization, all of the D2 domains in this dodecamer structure were also found to be free of nucleotide ( Figure S8 ).…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation